2015
DOI: 10.1016/j.catena.2014.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Holocene flooding and climate change in the Mediterranean

Abstract: Mediterranean fluvial hydrology is characterised by decadal-to-multi-centennial length wet and dry episodes with abrupt transitions related to changes in atmospheric circulation. Since the mid-1990s site-based flood chronologies from slackwater deposits in bedrock rivers and regionally aggregated flood histories from alluvial deposits have developed increasingly higher resolution chronological frameworks, although regional coverage is still uneven. This paper analyses the spatial and temporal distribution of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
130
1
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 173 publications
(150 citation statements)
references
References 166 publications
11
130
1
8
Order By: Relevance
“…That is a clear indication of positive synergies between human impact and humid periods leading to increased sediment delivery and denudation. Therefore, as Benito et al (2015) also showed, human impacts on runoff and sediment production at a catchment scale in small basins cannot be omitted at least over the last millennium.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…That is a clear indication of positive synergies between human impact and humid periods leading to increased sediment delivery and denudation. Therefore, as Benito et al (2015) also showed, human impacts on runoff and sediment production at a catchment scale in small basins cannot be omitted at least over the last millennium.…”
Section: Discussionmentioning
confidence: 95%
“…These activities have varied significantly both in time and space, providing heterogeneity in the hydrological response (Benito et al, 2015). All the lacustrine and experimental catchments, except San Salvador, constitute a highly modified landscape by anthropogenic activities (agriculture and livestock industry) during the last 1000 years.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the early Holocene climate was generally dry except for short pulses of higher fluvial activity reported in the Durance and southern Alps rivers (Arnaud-Fassetta et al, 2010). A marked cooling trend is observed with a major change around 7500 a cal BP (Fletcher and Sánchez Goñi, 2008) corresponding to humid conditions in the Iberian peninsula (Benito et al, 2015). The mid-Holocene (from ca.…”
Section: Holocene Paleohydrology In the Western Mediterraneanmentioning
confidence: 98%
“…Complex climate regimes result from external forcing (orbital, solar activity, volcanism) as well as from internal modes of atmospheric variability such as the North Atlantic Oscillation, east Atlantic, east-Atlantic-westRussian or Scandinavian modes (Josey et al, 2011;Magny et al, 2013). In the NW Mediterranean, the Holocene fluvial hydrology has been reconstructed using major hydrological events (extreme floods and lake levels) recorded in lake and fluvial sediments (Arnaud et al, 2012;Benito et al, 2015;Magny et al, 2013;Wirth et al, 2013). Overall, the early Holocene climate was generally dry except for short pulses of higher fluvial activity reported in the Durance and southern Alps rivers (Arnaud-Fassetta et al, 2010).…”
Section: Holocene Paleohydrology In the Western Mediterraneanmentioning
confidence: 99%
“…Recent studies suggest that climate change may have an impact on the triggering of flash floods and that the occurrence may increase at the global scale (Beniston, 2009;Giorgi et al, 2011). Specifically in Spain, Benito (2006) and Benito et al (1996Benito et al ( , 2015 have reported on the flood sensitivity of Spanish rivers to climate change and suggest that variations in climate characteristics may increase the irregularity of the flood regime and droughts and thereby favor the generation of flash floods in Mediterranean basins. Changes in precipitation may have a direct impact in the future occurrence of extreme hydrological events Gobiet et al, 2014;Stoffel and Huggel, 2012;Stoffel et al, 2014a), which could in turn affect the future development of mountain environments (Beniston et al, 2012).…”
Section: Introductionmentioning
confidence: 99%